2017
DOI: 10.3390/su9091598
|View full text |Cite
|
Sign up to set email alerts
|

Human Mobility Analysis for Extracting Local Interactions under Rapid Socio-Economic Transformation in Dawei, Myanmar

Abstract: Understanding human mobility patterns provides knowledge about impacts of a socio-economic transformation in a rapidly urbanizing environment. This study assesses a long-term mobility data which uses a face-to-face questionnaire and GPS logger-based method of data collection for extracting socio-economic impacts from the rapid transformation. Conversion of mobility related information such as travel distance, direction, and time from the questionnaire survey into spatiotemporal information was carried out by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Since the transformation by ASGM in remote rural areas is associated with influxes of miners who live at mining camps, as described in the Introduction, the spatial distribution of built-up areas was extracted as a significant indicator of the transformation of the ASGM camps resulting from large influxes of miners. Built-up areas can be defined by their physical aspects, such as predominantly human-constructed elements [ 42 ], as in this study. A number of spectral indices, including the Urban Index (UI) [ 43 ], Normalized Difference Built-up Index (NDBI) [ 44 ], Index-based Built-up Index [ 45 ], Built-up Area Extraction Method [ 46 ], Enhanced Built-up and Bareness Index [ 47 ], Band Ratio for Built-up Area [ 48 ], Built-up Index [ 49 ], Normalized Difference Vegetation Index (NDVI) [ 34 ], and Automated Built-up Extraction Index [ 50 ], have been developed to extract built-up areas from satellite imagery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the transformation by ASGM in remote rural areas is associated with influxes of miners who live at mining camps, as described in the Introduction, the spatial distribution of built-up areas was extracted as a significant indicator of the transformation of the ASGM camps resulting from large influxes of miners. Built-up areas can be defined by their physical aspects, such as predominantly human-constructed elements [ 42 ], as in this study. A number of spectral indices, including the Urban Index (UI) [ 43 ], Normalized Difference Built-up Index (NDBI) [ 44 ], Index-based Built-up Index [ 45 ], Built-up Area Extraction Method [ 46 ], Enhanced Built-up and Bareness Index [ 47 ], Band Ratio for Built-up Area [ 48 ], Built-up Index [ 49 ], Normalized Difference Vegetation Index (NDVI) [ 34 ], and Automated Built-up Extraction Index [ 50 ], have been developed to extract built-up areas from satellite imagery.…”
Section: Methodsmentioning
confidence: 99%
“…A number of spectral indices, including the Urban Index (UI) [ 43 ], Normalized Difference Built-up Index (NDBI) [ 44 ], Index-based Built-up Index [ 45 ], Built-up Area Extraction Method [ 46 ], Enhanced Built-up and Bareness Index [ 47 ], Band Ratio for Built-up Area [ 48 ], Built-up Index [ 49 ], Normalized Difference Vegetation Index (NDVI) [ 34 ], and Automated Built-up Extraction Index [ 50 ], have been developed to extract built-up areas from satellite imagery. Furthermore, human visual interpretation was also used [ 42 ]. Previous studies found that NDBI [ 51 , 52 ] and UI [ 53 , 54 ] are most sensitive in retrieving built-up areas, although these have mainly been used in urban studies.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the built-up areas were defined based on their physical aspects, such as a built-up environment consisting mostly of human-constructed elements [33]. A number of spectral indices, together with human visual interpretation [33][34][35][36][37][38][39][40][41], were employed to detect built-up areas using remote-sensing technology.…”
Section: Extraction Of Built-up Areas Ntl and Precipitation Datamentioning
confidence: 99%
“…In this study, the built-up areas were defined based on their physical aspects, such as a built-up environment consisting mostly of human-constructed elements [33]. A number of spectral indices, together with human visual interpretation [33][34][35][36][37][38][39][40][41], were employed to detect built-up areas using remote-sensing technology. Previous studies found that the Normalized Difference Built-up Index (NDBI) [42,43] and the Urban Index (UI) [44,45] had high sensitivities for retrieving built-up areas; however, these have been employed mainly in urban studies.…”
Section: Extraction Of Built-up Areas Ntl and Precipitation Datamentioning
confidence: 99%